TANTANGAN PERPUSTAKAAN PERGURUAN TINGGI DALAM ERA GLOBALISASI YANG KOMPETITIF UNTUK SIAP MENGHADAPI AKREDITASI - Hakim, Lukmanul (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2009)
A library has significant role at education institution not only as a supporting program for the three duty of university: as well, it is one of the elements that decide institution status in accreditation test, especially in provate university. The competitive condition amon private university has pushed the library to take part together in succeeding their institutional program. A good library will be visited by students from various university, “this will promote its institution name indirectly”. The problem now is, do the present private universities library now, are able to give an active role to face their challenge in this competitive globalization era and ready to ace accreditation test? Key word: private university, library, accreditation